WOntoVLab: um processo para autoria de laboratórios virtuais baseado em workflows e ontologias - Cugler, Daniel Cintra (2010)
Virtual laboratories can be used by educational institutions to facilitate and enrich the learning of specific procedures, however they can be also used by industry in demonstrations, tests and trainings. Laboratorial practices are normally performed in physical laboratories, but sometimes it is necessary to afford a great amount of money to acquire apparatuses and physical space to build them. In this context, virtual laboratories have been used as a solution at less cost to provide environments that support the simulation of experiments in computers. However, in order to provide such an environment, it is recommended that users not only create experiments that require the accomplishment of a protocol (guide), but also be able to identify different possibilities of execution of a same task, considering similar apparatuses and procedures. In this context, it is defined in this research the WOntoVLab, a virtual laboratory authorship process based on workflows and ontologies that performs recommendations of apparatuses in the authorship process and also represents experiment protocols based on semantic vocabulary and alternative steps. It is also detailed a estudy case performed in the molecular biology domain, focused in the DNA extraction experiment. The study case is performed using the virtual laboratory prototype developed, which is totally based in the WOntoVLab process. Lastly, it is mentioned the contributions of this research: the WOntoVLab process, WPF framework and WPF-WS framework.